The Spirit of Socially Engaged Buddhism: Public Welfare Operations of Rescue Groups Supported by Buddhist Institutions in the Northern Region of Thailand - Panyachit, Saichol; Sirisawad, Natchapol (Journal of International Buddhist Studies, 2025)
Amidst the dangers of people's social lives in a context where Buddhist institutions drive themselves toward becoming socially engaged in Buddhism, this research draws on a purposive sampling of 30 key informants—Buddhist monks and volunteer rescue team members in northern Thailand—who are directly involved in rescue operations. Thematic analysis (TA) was then applied to identify core themes. Employing qualitative research methods, the study aims to gain a deep understanding of rescue groups' public welfare operations, focusing on two important aspects. First, it investigates the operating model of the public welfare operations of the rescue groups supported by Buddhist institutions. And secondly, it analyzes the roles of the public welfare operations of the rescue groups. This article collates sociological perspectives of this effort with Buddhist concepts. The research findings indicate that assisting, supporting, and integrating public welfare operations are at the heart of the operating model of rescue groups that are supported by Buddhist institutions. Assisting refers to direct aid by Buddhist institutions without intermediaries; supporting involves mobilizing resources to enable others to assist; and integrating positions the institution as a social network node, coordinating multi-sectoral participation. Its implications are apparent in three key roles: as initiators in problem-solving, as centers for coordinating cooperation, and as facilitators in strengthening the Buddhist institutions.